Pengaruh Faktor Fundamental terhadap Return Saham Perusahaan Kategori Jakarta Islamic Index di Bursa Efek Indonesia - Putri Deliana Febrianti; Dadang Hermawan; Mochamad Edman Syarief; Lya Amailiya (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to investigate the impact of the fundamental elements of the company as seen through financial ratios, including the Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings Per Share (EPS), Price Earning Ratio (PER), and macroeconomic variables Inflation and BI Rate on stock returns of companies in the Jakarta Islamic Index category on the Indonesia Stock Exchange in the period 2015-2020. Panel data regression analysis is the data analysis method employed, while E-Views 9 is the data analysis tool. According to the study's findings, the Jakarta Islamic Index's stock returns are significantly and negatively impacted by the BI Rate. Meanwhile the Jakarta Islamic Index's stock returns are not significantly impacted by CR, DER, ROE, EPS PER, or inflation.